CONQUEROR - Tampubolon, Aaron Tristan Immanuel (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Conqueror is a musical composition inspired by the story of a judge in the Bible named Gideon in his battle against the Midianites. The method of creation in this music composition work uses stages based on L.H Chapman's theory, namely, efforts to find ideas, refine, develop and solidify initial ideas, and the realization of the work. The concept of Conqueror music is done with a modern music approach which is then packaged into three parts where each part has its own story which is then implemented into the instrument work.